MODIFICATION RECYCLE JUTE FIBRE WASTE FOR BULLET PROOF VESTS - Dewi Suliyanthini; Riza Wiryawan Jonathan; siti Nursetiawaty; Aam Amaningsih (Jurnal Green Growth dan Manajemen Lingkungan, 2014)
This research uses experimental methods to find a formula modifications pure jute (Corchorus capsularis) and Javajute for textile composition strong and resistant to bullets, with the use of resin carbonanotubes (CNT) and tensile strength testing of physical evaluation and test-fired a fabric that can be accounted for laboratory. With methodology Kuantitatif Research and Develipment (R and D). Experiment by processing waste recycling Jute / Javajute into textile products. Jute / Javajute are plants that are often found on the coast of Indonesia, and has not done a lot of processing, it is generally discarded as useless waste. With experimental textile processing, waste jute / javajute be converted into bullet resistant textile products. Long-term goal of this research is to get the right formula in terms of kompisisi fiber, basket type, and CNT resin composition, thereby answering a concern for domestic products and recycling waste back also unearth medium economic enterprises and SMEs in terms of plantation.The experimental results obtained that the tensile strength of jute fabric with or without CNT> 100 kg, and the tensile strength of the fabric javajute without CNTs> 97 kg, Javajute + CNT> 100kg.with Yarn Number Ne 11. Test results using a pistol bullet caliber Revolfer II Internationa Standard Evaluationl (SII), weighs 9 gram bullet diameter of 9 mm bullets, bullet time speed of 341 m / s, Jute cloth + produced CNTs with 32 layers of clay sculpture penetration depth of 12 mm. Jute cloth non CNT 12mm. Cain jute ResinCNT, 3,9kg + 12 mm. Cain jute non CNT 0,7mm. The experiment its goals if onlu 0,4 mm bullet . For comparison in the Army agency, usually the fabric used for bulletproof Highcon types of PET imported products with a very high price. With a composition of 16-32 layers of PET weight between 21.9 to 30 gr. Where is the time of the shooting bullets lodged in the lining of the 11 for pistol caliber II and for rifle bullets lodged in the lining of 23-27. And than eksperiment for bullet vets ptoof FN25 pistol hurahara with sample same its success cannot mannequien body. Until linning 6 for jute CNT and linning 8 sample Jute. Weigth sample jute CNT 2.9 kg 32 linning CNT resin 1%, Weigth sample jute original 2,2 kg 32 linning. This is a succes for pistol level 5.